Frequency of Quinolone Resistance and qnrB and qnrC Genes in Clinical Isolates of Klebsiella pneumoniae - Maryam Moghadasi; Mohsen Mirzaee; Mohammad Reza Mehrabi (Journal of Medical Bacteriology, 2017)
Background:   Klebsiella pneumoniae is among the most common and significant agents of community and hospital-acquired infections. Plasmid mediated quinolone resistance (PMQR) was increasingly identified in Enterobacteriaceae family worldwide. Plasmid-mediated quinolone resistance (PMQR) was first reported in 1998 from a Klebsiella pneumoniae isolate in the USA. Till date, five Qnr proteins have been identified; QnrA, QnrB, QnrC, QnrD and QnrS. Quinolone are broad spectrum antibiotics the resistant to which has increasingly been reported among many bacterial species including Klebsiella. The aim of this study was the antibiotic resistance profile was determined based on resistance and molecular characterization of qnrB and qnrC genes in Klebsiella pneumoniae clinical isolated.